Frequence Et Facteurs Associes Aux Accouchements Prematures Au Centre Hospitalier Universitaire Et Departemental Du Borgou Alibori Au Benin - N.F.M., Hounkponou; A., Tonato Bagman; AY., Ahouingnan; S., Gbevo; H., Laourou; M., Vodouhe; RI, Sidi; A., Obossou; K., Salifou (European Scientific Journal, ESJ, 2017)
Introduction: The premature birth constitutes a major cause of the neonatal and maternal mortality and morbidity and it occurs between 28 weeks of amenorrhoea and 36 weeks plus six days. Objectives: It is to determine the frequency and the factors associated to the premature at the maternity at the Departmental and Teaching Hospital of Borgou. Tool and methodological approaches: It is about an analytical and descriptive retrospective study carried out at the Hospital Teaching Centre of Borgou. The study has been conducted from the 1st January to 30th June 2016. Results: From the 665 retained deliveries, 119 were premature births, be a frequency of 17.89%. The bracket age of 20-34 years was the most represented with 69, 75%. The pauci gests and the primipara were respectively in 36.13% and 40.34% of the cases. The factors of risk such as premature rupture of membranes (PRM; p=0.00001), the haemorrhagic prævia placenta (p=0.0001), the multiple pregnancies (p=0.000003) were associated with prematurity. Conclusion: The prematurity constitutes a problem of public health in parakou and is responsible for the heavy consequences on the still-born. Hence, the interest of a better agreement to pay the medical expenses of the factors of risk permitting the reduction of its repercussion.